P401 REMOTE COUNSELING ROLE DURING COVID–19 PANDEMIC IN SECONDARY PREVENTION AFTER ACUTE CORONARY SYNDROME. (18th May 2022) - Lordi, R; Veronese, S; Ferro, A; Piccinini, A; Piva, T; Zerbini, V; Raisi, A; Mandini, S; Grazzi, G; Sassone, B; Pasanisi, G
Abstract: Introduction: Patients affected by acute coronary syndrome are usually referred to center–based secondary prevention programs where they are enrolled in physical activity programs and received indications about cardiovascular risk factors control. COVID–19 pandemic induced the emanation of restrictions in people's mobility, ban on gathering and the obligation of social distancing. This made it difficult to maintain such group meetings in presence. Methods: After hospitalization for acute coronary syndrome in Cardiology Unit of the AUSL of Ferrara, patients equipped with electronic devices were allowed to participate to remote counseling meetings on the digital platform LifesizeC. To improve participation, meetings were organized monthly (in order to gradually include new discharged patients) and involving caregivers (if patients weren't able to access the web app). Information on regular physical activity benefits were provided. In particular, the F.I.T.T. principle (Frequency, Intensity, Type, Time) has been explained and Borg's exertion scale was illustrated to be used in autonomy. Furthermore, there were provided recommendations about the need of a proper warm– up/cool–down, the possibility to wear a heart rate monitor and the early recognition of symptoms and warning signs. To complete health education, there were given information about correct nutrition, risk factors control and correct assumption of pharmacological therapy. Results: All patients showed interest in the topics analyzed, asking various questions during the meetings. They also stated that they were strongly motivated to undertake regular physical activity having received convincing explanations on its usefulness and safety. Conclusions: Remote counseling meetings obtained a high approval rating and the moments of discussion with the speakers were particularly well attended. The prescription of physical exercise in secondary prevention can follow innovative telemonitored approaches, which could be maintained even after COVID–19.